1974
DOI: 10.1111/j.1365-2621.1974.tb17980.x
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic Degradation of Anthocyanins: The Role of Sweet Cherry Polyphenol Oxidase

Abstract: S An enzymatic system capable of degrading cyanidin‐3‐glucoside in the absence of phenols is present in the skin of sweet cherries; contrarily, the pulp homogenate degraded the anthocyanin only in the presence of phenols. The degradation of this pigment as a function of pH was studied for two polyphenol oxidases isolated from the fruit pulp on DEAE‐cellulose with chlorogenic acid, D (+) catechine and pyrocatechol substrates. The decoloration was influenced by the anthocyanin structure at different pH and by th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
1
1

Year Published

1996
1996
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(45 citation statements)
references
References 24 publications
2
41
1
1
Order By: Relevance
“…The existence of two peaks in gel filtration chromatography proves this result, as well. Generally, 2-3 PPO isoenzymes have been detected in fruits, such as apple (Constantinides et al, 1967), pear (Rivas and Whitaker, 1973), cherry (Pifferi and Cultrera, 1974), and banana (Palmer, 1963). Since, there is no research on dog-rose PPO isoenzymes, it is not possible to compare our results, but there are similarities with previous studies on other fruits indicated above.…”
Section: Resultssupporting
confidence: 87%
“…The existence of two peaks in gel filtration chromatography proves this result, as well. Generally, 2-3 PPO isoenzymes have been detected in fruits, such as apple (Constantinides et al, 1967), pear (Rivas and Whitaker, 1973), cherry (Pifferi and Cultrera, 1974), and banana (Palmer, 1963). Since, there is no research on dog-rose PPO isoenzymes, it is not possible to compare our results, but there are similarities with previous studies on other fruits indicated above.…”
Section: Resultssupporting
confidence: 87%
“…41 However, we did not see any correlation between PPO activity and postharvest anthocyanin content. This can be explained by the fact that anthocyanins are located inside the vacuoles whereas PPO is located in the cytosol, so that the two only come into contact late in the senescence period owing to cellular breakdown.…”
Section: Oxidative Enzymesmentioning
confidence: 40%
“…The most common anthocyanin degrading enzymes are glycosidases, which break the covalent bond between the glycosyl residue and the aglycone of an anthocyanin pigment, resulting in the degradation of the highly unstable anthocyanidin (Huang, 1955;Huang, 1956). Peroxidases and phenolases, such as phenol oxidases and polyphenol oxidases, which both are found naturally in fruits and berries themselves, are also common anthocyanin degradating enzymes (Kader, Rovel, Girardin, & Metche, 1997;Pifferi & Cultrera, 1974).…”
Section: Enzymesmentioning
confidence: 99%